Duct quiet zones utilization for an enhancement the acoustical air-condition noise control - Mahmoud Kamel, Mohamed; Soliman Ahmed Said, EL-Sayed; Mohamed AL-Sagheer, Ragab (Institute of Advanced Engineering and Science, 2022)
This paper investigates the duct’s noise distribution pattern due to the heating, ventilation, and air conditioning systems. This study is considering the longitudinal sound wave distribution that can permit a higher reduction of these heating, ventilation, and air conditioning systems duct noise. The proposed technique is depending on the lowest sound pressure level points in the duct or duct quiet zones. Moreover, each heating, ventilation, and air conditioning systems duct has several quiet zones, depending on the sound pressure level of the fan noise source and the duct length as well as the duct diameter. Furthermore, the noise standing wave has a wavelength (λ) which is the distance between two successive quiet zones. This work utilizes orthogonal acoustical noise with the standing wave via feed-forward control speakers. This system confirmed that the distance (λ) is linearly proportional to the duct source noise level. This system noise reduction enhancement has been fulfilled by installing further noise feed-forward control speakers at different duct quiet zones. The system simulation results were displaying satisfactory agreement with the field experimental results.